2008
DOI: 10.1097/ijg.0b013e318133fc5b
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Myocilin Asn480Lys Glaucoma Causative Mutation Arises De Novo in a Family of Andean Descent

Abstract: In the study of MYOC variants in 11 POAG Peruvian families, we have found a family of ethnically admixed origin with polymorphism Arg76Lys and a family of Andean descent bearing a third event of the Asn480Lys, the MYOC mutation that has been reported in the highest number of POAG patients (>80 cases). Analysis of this family could contribute with information about disease manifestation, progression, and treatment response in the context of a distinct genetic background and also climatic, altitude, and socioeco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
3
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 24 publications
1
8
3
3
Order By: Relevance
“…Diagnosis JOAG (Brézin et al, 1998; Mimivati, Nurliza, Marini, & Liza‐Sharmini, 2014; R. Rose et al, 2011) POAG (Adam et al, 1997; Brézin et al, 1998; Guevara‐Fujita et al, 2008; Hulsman et al, 2002; Melki, Belmouden, et al, 2003) …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Diagnosis JOAG (Brézin et al, 1998; Mimivati, Nurliza, Marini, & Liza‐Sharmini, 2014; R. Rose et al, 2011) POAG (Adam et al, 1997; Brézin et al, 1998; Guevara‐Fujita et al, 2008; Hulsman et al, 2002; Melki, Belmouden, et al, 2003) …”
Section: Introductionmentioning
confidence: 99%
“…POAG (Adam et al, 1997; Brézin et al, 1998; Guevara‐Fujita et al, 2008; Hulsman et al, 2002; Melki, Belmouden, et al, 2003)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tato mutace byla zjištěna i u dalších rodinných příslušníků IV:2, IV:4, IV:7, IV:9, V:3, V:5, V:6 a V:7 (Obrázek 2B). Také varianta c.1440C>A byla v souvislosti s výskytem PGOÚ opakovaně popsána [13][14][15][16]. Variantu jsme klasifikovali jako patogenní, stejně jako databáze Clinvar, kde je interpretována jako kauzální pod identifikátorem VCV000007951.1.…”
Section: Výsledkyunclassified
“…The study of MYOC (OMIM #601652) (locus GLC1A ) has identified both known mutations in European and African‐American populations, as well as novel mutations. Interestingly, these variants are correlated with African ancestry (Chincha and Cañete) and the novel are recurrent in Peru, probably indicating an autochthonous founder effect (Guevara‐Fujita et al, ; Mendoza‐Reinoso et al, ). Another disease studied at CGBM‐USMP is retinitis pigmentosa—which has a genetic heterogeneity, with more than 70 genes—in approximately 100 Peruvian families, having identified the causative mutation in 30 of them.…”
Section: Basic and Translational Research On Genetics And Genomicsmentioning
confidence: 99%